Isolation, identification and genotypic and phenotypic characterization of Arcobacter spp. isolated from Minas frescal cheese and raw milk - Bravo, Melina Luz Mary Cruzado (2020)
Arcobacter is considered an emerging foodborne pathogen which is associated with gastroenteritis, persistent diarrhea and bacteremia in humans. Similarly, in animals, it can cause abortion, infertility and diarrhea. Isolation of this pathogen from asymptomatic animals is also frequent as they are natural reservoirs. Animal foods are probably the main route of transmission to humans. Studies carried out in different countries have indicated that patients with gastroenteritis caused by Arcobacter is the fourth most common isolate. Currently, in Brazil, there is a great occurrence of gastrointestinal diseases without identification of the etiologic agent. Arcobacter was isolated from Minas frescal cheese and raw bovine milk in São Paulo, Brazil In this work, 98 samples of Minas frescal cheese and 103 samples of raw bovine milk were analyzed and data showed 10.2% and 16.5% occurrence respectively. All isolates were identified as A. butzleri and the presence of Arcobacter was correlated with the moisture (cheese) and total coliforms and mesophilic bacteria counts (milk). Subsequently, 36 strains of A. butzleri were analyzed for virulence, resistance to antibiotics and the formation of biofilms. Then, the formation of biofilms in eight isolates was observed on different contact surfaces commonly used in dairy procesing plants. Finally, the influence of other factors on the production of A. butzleri biofilm was evaluated. High genotypic diversity, sensitivity to ciproploxacin antibiotics, erythromycin and azithromycin were observed. Strains from raw milk showed the highest biofilm formation ability. Stainless steel presented the greatest cellular adhesion. With the information obtained about Arcobacter isolates, it is possible to develop better strategies to avoid contamination in ready-to-eat foods, such as Minas fresal cheese, and to provide valuable information on proper heat treatment conditions, cleanliness and sanitation. Further research concerning the presence and activity of the Arcobacter genus is necessary in the whole dairy product chain.